Your Research Is Public Engagement: A Case for More Intentional Science Communication in Research With Human Subjects. - Vaughn, Charlotte (Journal of Experimental Psychology. General, 2026)
This article argues that experimental psychologists who conduct research with human subjects are in fact doing public engagement about the field with their participants whether they are aware of it or not. Researchers are missing opportunities to connect with public audiences by not being aware of and intentional about what their experiments communicate. Borrowing from science communication, the article discusses objectives that can serve as a guide in designing both experiments and debriefings with participant engagement in mind. Articulated as the research as engagement model, the article suggests that our research and broader impact goals can be well-served if we view each study participant not only as a data point but as an opportunity for public engagement. Public Significance Statement: Much of what we know about psychology comes from individual research participants completing experiments in the lab or online. Although members of the public encounter psychology by the thousands through these experiments, many do not gain any meaningful appreciation of the science they are contributing to or may leave an experiment with mistaken impressions about the research or the field. This article makes the argument that researchers should think more about what their experiments communicate with their participants and encourages researchers to engage with their participants about psychology as part of the research process itself. Described as the research as engagement model, the shift in thinking presented in this article invites psychological scientists to view each study participant not only as a data point but as an opportunity for public engagement.